ANALISIS PEMBELAJARAN BAHASA SUNDA PADA SISWA KELAS V SDN KENCANA 3 KOTA BOGOR - Rustandi, Yuyus; Putro, Sasongko S (Media Bahasa, Sastra, dan Budaya Wahana, 2018)
Abstract Communicating for the international level, the most commonly used language is English, for national level communication is Indonesian, and for communication at the regional level the regulators generally use the local language. Sundanese is the same as other regional languages, is at the third level of world language use, so many students consider local language subjects in West Java to be less interesting to learn. In the level of education, efforts to change these assumptions, Sundanese language teachers should be able to get around so that students can become interested in local languages by making adequate learning strategies. Keywords: Analysis of Primary School Language Learning